Time Scales of Ecosystem Impacts and Recovery Under Individual and Serial Invasions - Vadim A. Karatayev; Lars G. Rudstam; Alexander Y. Karatayev; Lyubov E. Burlakova; Boris V. Adamovich; Hanna A. Zhukava; Kristen T. Holeck; Amy L. Hetherington; James R. Jackson; Csilla Balogh; Zoltán Serfőző; Christopher W. Hotaling; et al. (Ecosystems, 2023)
The impacts of species invasions can subside over time as ecosystems ‘adapt’ and invaders decline or increase over time as additional species invade. The character and timescales of invasion impacts provide important insights into ecosystem dynamics and management. Yet long-term studies of invasion impacts remain rare and often confound invasive species impacts with coincident environmental change. One way to address this challenge is to ask: what ecological changes over time since invasion are recapitulated in ecosystems that span a range of conditions, are located in different regions, and were invaded in different decades? We synthesize many-decade time series across seven ecosystems to resolve shared changes in seven key ecosystem features following invasion by zebra mussels and subsequent invasion by quagga mussels. These two congeners are among the most widespread invasive species that re-engineer and increasingly co-invade freshwater ecosystems. Seven polymictic shallow lakes with long-term data sets reveal remarkably similar trends, with the strongest ecosystem impacts occurring within 5–10 years of zebra mussel invasion. Surprisingly, plankton communities then exhibited a partial, significant recovery. This recovery was absent, and impacts of initial invasion amplified, in four lakes where quagga mussels outcompeted zebra mussels and more completely depleted phytoplankton. Thus, we show that the ecosystem impacts of invasive species can subside over time but amplify with serial introductions of competing, even closely similar, taxa.